2011
DOI: 10.1007/s00011-010-0306-1
|View full text |Cite
|
Sign up to set email alerts
|

SHP-dependent and -independent induction of peroxisome proliferator-activated receptor-γ by the bile acid sensor farnesoid X receptor counter-regulates the pro-inflammatory phenotype of liver myofibroblasts

Abstract: The present study provides a molecular basis for the physiological cross-talk between FXR and PPARγ pathways in HSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…Therefore, we investigated the influence of squalene on gene expression of three major MMPs (MMP-1, MMP-3 and MMP-9). As PPARγ agonists have been shown to inhibit LPS-mediated MMPs and pro-inflammatory cytokines (Renga et al, 2011;Wang et al, 2011), our study also undertook to explore whether squalene can affect PPARγ gene expression in LPS-treated cells. As shown in Fig.…”
Section: Squalene Down-regulates Mmps and Up-regulates Pparγ Gene Expmentioning
confidence: 99%
“…Therefore, we investigated the influence of squalene on gene expression of three major MMPs (MMP-1, MMP-3 and MMP-9). As PPARγ agonists have been shown to inhibit LPS-mediated MMPs and pro-inflammatory cytokines (Renga et al, 2011;Wang et al, 2011), our study also undertook to explore whether squalene can affect PPARγ gene expression in LPS-treated cells. As shown in Fig.…”
Section: Squalene Down-regulates Mmps and Up-regulates Pparγ Gene Expmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the expression/activity of PPARs is positively modulated by the nuclear receptor FXR (Farnesoid X Receptor) [180]. These authors identified, in the PPAR gene promoter, a sequence containing FXR-responsive element (FXRE).…”
Section: Ppar In Hepatic Stellate Cellsmentioning
confidence: 99%
“…The same authors also demonstrated the role of FXR-PPAR crosstalk in inhibiting cytokine production and regulating inflammatory response of HSCs exposed to LPS. The cross-talk between these two nuclear receptors represses, in turn, the synthesis of collagen-and -SMA expression in activated HSCs [180].…”
Section: Ppar In Hepatic Stellate Cellsmentioning
confidence: 99%
“…Further, fenofibrate, a PPARα agonist, increases SHP gene expression in the liver and protects from fibrosis induced by TGF-β1 and a methionine and choline-deficient diet through AMPK mediated induction of SHP gene expression9. Loss of SHP is also known to increase sensitivity to liver damage and fibrosis induced by bile duct ligation (BDL)10 establishing a major role for this gene in modulating transactivation of HSCs11.…”
mentioning
confidence: 99%
“…Because its mechanistic role in liver fibrosis811, identification of SHP ligands and molecular pathways regulated by SHP may lead to discovery of new treatments for liver diseases. Consistent with this concept, SHP ligands were actively searched1213.…”
mentioning
confidence: 99%